2013
DOI: 10.3389/fncom.2013.00147
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent and coordinated shift in performance between implicit and explicit skill learning

Abstract: It has been reported recently that while general sequence learning across ages conforms to the typical inverted-U shape pattern, with best performance in early adulthood, surprisingly, the basic ability of picking up in an implicit manner triplets that occur with high vs. low probability in the sequence is best before 12 years of age and it significantly weakens afterwards. Based on these findings, it has been hypothesized that the cognitively controlled processes coming online at around 12 are useful for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
262
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(272 citation statements)
references
References 47 publications
10
262
0
Order By: Relevance
“…Findings suggested a stronger learning effect in the young groups (4‐ to 12‐year‐olds) which gradually declined over the older groups (14‐ to 85‐year‐olds). These findings were confirmed by a second paper of the same group, using partly the same group of participants (Németh, Janacsek, & Fiser, ), and are in line with a previous study (Fischer, Wilhelm, & Born, ). Janacsek et al .…”
Section: Typical Developmentsupporting
confidence: 91%
“…Findings suggested a stronger learning effect in the young groups (4‐ to 12‐year‐olds) which gradually declined over the older groups (14‐ to 85‐year‐olds). These findings were confirmed by a second paper of the same group, using partly the same group of participants (Németh, Janacsek, & Fiser, ), and are in line with a previous study (Fischer, Wilhelm, & Born, ). Janacsek et al .…”
Section: Typical Developmentsupporting
confidence: 91%
“…We know that children are able to explicitly understand the concept of probability by 9 or 10 years of age (e.g., Nikiforidou & Pange, 2010;Piaget & Inhelder, 1975). However, their ability to extract and explicitly express statistical probabilities continues to develop for many more years (e.g., Eppinger, Mock, & Kray, 2009;Hämmerer, Li, Müller, & Lindenberger, 2011;Janacsek, Fiser, & Nemeth, 2012;Nemeth, Janacsek, & Fiser, 2013). If these differences in processing probabilistic information also apply to implicitly extracting information about environmental regularities, then we would expect to find that acquiring contextual cueing by children is more affected by the introduction of noise than is the contextual cueing of adults.…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, the authors observed a peak in task performance before the age of 12, after which performance dropped significantly. In another version of the task, however, where participants were explicitly made aware of the repetition, using instructions and visual cues, they found no age‐dependent change in learning (Nemeth, Janacsek, & Fiser, ). Nonetheless, in this latter case, additional measures of explicit knowledge concerning the repeating sequence (using verbal reports) revealed a different age‐effect, with significantly better scores on explicit knowledge of the sequence after the age of 12.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, Nemeth et al. () argued that children's superiority in various skills might have its basis in underlying implicit‐learning abilities that shift to explicit‐learning mechanisms later in life (Poldrack & Packard, ). This might, in turn, be attributed to a neurological change at the level of two separate long‐term memory systems, namely an early developed basal‐ganglia system (the procedural memory system), that is involved in implicit skill learning, and the late maturing frontal/medial‐temporal circuits (the declarative memory system), that is assumed to rely on explicit attention processes (Perez, Peynircioglu, & Blaxton, ; Robertson, ; Squire, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation